2012
DOI: 10.1007/s00213-012-2853-3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional valence and context of social influences on drug abuse-related behavior in animal models of social stress and prosocial interaction

Abstract: Rationale Social factors are important determinants of drug dependence and relapse. Objectives We reviewed preclinical literature examining the role of social experiences from early life through the development of drug dependence and relapse, emphasizing two aspects of these experiences: 1) whether the social interaction is appetitive or aversive and 2) whether the social interaction occurs within or outside of the drug-taking context. Methods The models reviewed include neonatal care, isolation, social de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 264 publications
(317 reference statements)
2
72
0
Order By: Relevance
“…Other research has shown that repeated stress can enhance amphetamine-induced facilitation of ICSS (Lin et al, 2002), whereas effects of cocaine and THC were not altered by olfactory bulbectomy or repeated stress, respectively (Slattery et al, 2007;Fokos and Panagis, 2010). Together, these results illustrate the potential for differential effects of stress as a modulator of abuserelated drug effects in ICSS procedures, but given the prominent role of stress as a risk factor in drug abuse (Neisewander et al, 2012;Volkow et al, 2012), this is a relatively undeveloped theme of research.…”
Section: A Statesmentioning
confidence: 61%
“…Other research has shown that repeated stress can enhance amphetamine-induced facilitation of ICSS (Lin et al, 2002), whereas effects of cocaine and THC were not altered by olfactory bulbectomy or repeated stress, respectively (Slattery et al, 2007;Fokos and Panagis, 2010). Together, these results illustrate the potential for differential effects of stress as a modulator of abuserelated drug effects in ICSS procedures, but given the prominent role of stress as a risk factor in drug abuse (Neisewander et al, 2012;Volkow et al, 2012), this is a relatively undeveloped theme of research.…”
Section: A Statesmentioning
confidence: 61%
“…For example, pair bonding and environmental enrichment can serve as a protective component to drug-seeking behavior (Aragona et al, 2007;Solinas et al, 2008;Gipson et al, 2011;Liu et al, 2011;Burkett and Young, 2012;Puhl et al, 2012). Conversely, social isolation or the removal of environmental enrichment can cause an increased vulnerability to drug seeking (Lu et al, 2003;Raz and Berger, 2010;Nader et al, 2012;Neisewander et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…These reviews have examined the neurobiological mechanisms at the nexus of social contact and drug self-administration (Bardo et al, 2013), the behavioral mechanisms mediating the effects of social contact on drug self-administration (Strickland and Smith, 2014), the intersection of emotional valance and social context in drug self-administration (Neisewander et al, 2012), and the effects of social contact on conditioned drug reward (Zernig et al, 2013). The primary objective of this mini-review is to provide an evaluation of several preclinical models of proximal social contact and their application to the study of drug self-administration (see Figure 1 for schematic overview of the described models).…”
Section: Introductionmentioning
confidence: 99%